1986
DOI: 10.1037/0096-3445.115.4.348
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the vague meanings of probability terms.

Abstract: Can the vague meanings of probability terms such as doubtful, probable, or likely be expressed as membership functions over the [0, 1] probability interval? A function for a given term would assign a membership value of /ero to probabilities not at all in the vague concept represented by the term, a membership value of one to probabilities definitely in the concept, and intermediate membership values to probabilities represented by the term to some degree. A modified pair-comparison procedure was used in two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
214
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 439 publications
(227 citation statements)
references
References 45 publications
12
214
0
1
Order By: Relevance
“…Perhaps the most carefully worked out model relating memory search to judging individual events is MINERVA-DM (Dougherty, Gettys, & Ogden, 1999). Rapoport, Zwick, and Forsyth (1986) pointed out, individuals understand probability terms as imprecise, rather than precise, quantifications of uncertainty. Wallsten et al suggested that phrase meaning might be represented more accurately in terms of membership functions (MFs) over the [0,1] probability interval.…”
Section: Choice Modelsmentioning
confidence: 99%
“…Perhaps the most carefully worked out model relating memory search to judging individual events is MINERVA-DM (Dougherty, Gettys, & Ogden, 1999). Rapoport, Zwick, and Forsyth (1986) pointed out, individuals understand probability terms as imprecise, rather than precise, quantifications of uncertainty. Wallsten et al suggested that phrase meaning might be represented more accurately in terms of membership functions (MFs) over the [0,1] probability interval.…”
Section: Choice Modelsmentioning
confidence: 99%
“…The intermediate value may be that which is judged more appropriate for the label than any other but this doesn't mean it is judged to be a perfect exemplar (membership=1). Wallsten et al [30] describe an experiment in the analysis of which "these scale values, normalized to be nonnegative with an arbitrary maximum of 1 … can be taken as the membership function". The key word is "arbitrary".…”
Section: Vaguenessmentioning
confidence: 99%
“…In contrast to the non-parametric individualized MF approach of Budescu and colleagues [5,12] we fit group MFs to obtain a generalized model of a certain population of subjects. Furthermore, our MFs are defined continuously such that in addition to the expansions of the class (c parameters) the MFs' shape (d parameters) carries information about the distribution of the empirical estimates.…”
Section: Step Two: Fuzzy Analysismentioning
confidence: 99%